A Novel Definition of L-Fuzzy Lattice Based on Fuzzy Set. (5th June 2013) - Zhang, Jun-Fang
Abstract : The concept of L -fuzzy lattice is presented by means of an L -fuzzy partially ordered set. An L -fuzzy partially ordered set A is an L -fuzzy lattice if and only if one of A [ a ], A [ a ], and A ( a ) is a lattice.